Efektivitas Proses Fitoremediasi Air Irigasi Tercemar Bahan Organik melalui Sistem Batch Culture menggunakan Hidromakrofita Lokal - Retnaningdyah, Catur; Arisoesilaningsih, Endang (JURNAL BIOLOGI INDONESIA, 2018)
ABSTRACTIrrigation water in Indonesia generally has polluted by organic matter due to human activities. The aim of study was to develop a package of phytoremediation technology that can effectively reduce organic pollutants in the irrigation water in order to ensure good quality of water irrigation to support organic farming. The study was conducted in greenhouses by planting some local emergent, submerged, floating-leaf hydromacrophytes and polyculture species using a batch culture system on a 30 L bucket with sand and gravel as a substrate. The study used a completely randomized design with the treatment were five types of hydromacrophytes (emergent such as Scirpus sp., Acorus calamus, Marsilea crenata; floating leaf macrophytes included Ipomoea aquatica, Azolla sp.; submerged such as Valisneria sp., Hydrilla verticilata; polyculture of the three hydromacrophytes, and controls without plant) which repeated three times at the same time. The effectiveness of the phytoremediation model for each treatment is determined by its ability to improve water quality as reflected by several physicochemical parameters of pH, DO, conductivity, turbidity, temperature, nitrate, orthophosphate, bicarbonate, BOD, TSS, TDS and TOM six days after incubation. Research results showed that batch culture for six days significantly reduced the organic matter content of irrigation water reflected from decreasing value of BOD, TOM, TSS, turbidity, nitrate, orthophosphate and bicarbonate levels. The six-day phytoremediation process in all treatments has not been able to increase the dissolved oxygen content in the water and has not been able to significantly reduce the conductivity and TDS. Hydromacrophytes submerged and polyculture were more effectively perform phytoremediation process compared with others.Keywords: Phytoremediation, local hydromacrophytes of emergent, submerged, and floating leaves, water pollution